2019
DOI: 10.1007/s11789-019-00099-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and proprotein convertase subtilisin/kexin type 9 inhibitors

Abstract: Lipoprotein(a) (Lp(a)) is an internationally accepted independent atherogenic risk factor. Details about its synthesis, many aspects of composition and clearance from the bloodstream are still unknown. LDL receptor (LDLR) (and probably other receptors) play a role in the elimination of Lp(a) particles. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors increase the number of available LDLRs and in this way very effectively reduce the LDL cholesterol (LDL-C) concentrations. As shown in controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…PCSK9 inhibitors-decrease Lp(a) by a mean of about 20% (ranging between 0 and 44%); in some patients a reduction cannot be achieved. In two prospective controlled large studies, both evolocumab and alirocomab induced a modest reduction of cardiovascular events which was the consequence of decreasing Lp(a) levels-independently of the effects on LDL-C [20]. Up to now, an elevation of Lp(a) is no accepted indication for this injection therapy.…”
Section: Lipidologistsmentioning
confidence: 99%
“…PCSK9 inhibitors-decrease Lp(a) by a mean of about 20% (ranging between 0 and 44%); in some patients a reduction cannot be achieved. In two prospective controlled large studies, both evolocumab and alirocomab induced a modest reduction of cardiovascular events which was the consequence of decreasing Lp(a) levels-independently of the effects on LDL-C [20]. Up to now, an elevation of Lp(a) is no accepted indication for this injection therapy.…”
Section: Lipidologistsmentioning
confidence: 99%
“…Therefore, in the ODYSSEY OUTCOMES trial, patients treated with alirocumab for a median of 33 months showed 1.1 mmol/L reduction in LDL-C level that it can be considered up to 22% reduction in risk for cardiovascular events [83]. Moreover, a 25% lipoprotein little (a) (Lp(a)) reduction has been observed in alirocumab and evolocumab treated patients at long term follow up [84]; probably due to the similarities between LDL and Lp(a), it can be catabolized using LDLR-mediated pathway, this possibility, however, remains to be addressed. Further follow-up is essential to clarify mAbs' long-term safety and efficacy.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Sowohl in Statinstudien als auch in PCSK9-Inhibitorstudien hat sich trotz der erzielten Absenkungen von LDL-Cholesterin Lp(a) als ein eigenständiger atherogener Risikofaktor etabliert [32,33]. PCSK9-Hemmer reduzieren den Lp(a)-Spiegel um ca.…”
Section: Interventionsstudienunclassified
“…PCSK9-Hemmer reduzieren den Lp(a)-Spiegel um ca. 20 % und haben sowohl in der FOURIER-Studie (mit Evolocumab) als auch in der ODYSSEY-OUTCOMES-Studie (mit Alirocumab) auf diese Weise zu einer signifikanten Reduktion der kardiovaskulären Morbidität beigetragen [33].…”
Section: Interventionsstudienunclassified